Humic acids enhance salt stress tolerance associated with pyrroline 5-carboxylate synthetase gene expression and hormonal alteration in perennial ryegrass (Lolium perenne L.) - Meng, Qiuxia; Yan, Min; Zhang, Jiaxing; Zhang, Qiang; Zhang, Xunzhong; Yang, Zhiping; Luo, Yuan; Wu, Wenli (Frontiers in Plant Science, 2023)
Humic acid (HA) has been used as an important component in biostimulant formulations to enhance plant tolerance to salt stress, but the mechanisms underlying are not fully understood. This study was to investigate the physiological and molecular mechanisms of HA’s impact on salt stress tolerance in perennial ryegrass (Lolium perenne L.). The two types of HA were extracted from weathered coal samples collected from Wutai County (WTH) and Jingle County (JLH) of Shanxi Province, China. The grass seedlings subjected to salt stress (250 mM NaCl) were treated with HA solutions containing 0.01% WTH (W/V) or 0.05% JLH (W/V), respectively. The HA treatments improved leaf photosynthetic rate (Pn), transpiration rate (Tr), and stomatal conductance (Gs) and reduced leaf oxidative injury (lower malondialdehyde content) and Pro and intercellular CO2 concentrations in salt-stressed perennial ryegrass. The HA treatments also reversed the decline in antioxidative enzymes ascorbate peroxidase (APX), catalase (CAT), peroxidase (POD), and superoxide dismutase (SOD) activity and improved growth and anti-senescence hormones indole-3-acetic acid (IAA) and brassinosteroid (BR). The HA treatments reduced the relative expression of P5CS and its downstream products proline (Pro) and the stress defense hormones abscisic acid (ABA), salicylic acid (SA), jasmonic acid (JA), and polyamines (PA). The results of this study indicate that the application of HAs may improve salt stress tolerance by regulating P5CS gene expression related to osmotic adjustment and increasing the activity of antioxidant enzymes and anti-senescence hormones in perennial ryegrass.